Are Fiscal Consolidation Episodes Helpful for Public Sector Efficiency? - António Afonso; José Alves (Center for Economic Studies and ifo Institute (CESifo), 2022)
We assess the consequences of fiscal consolidation episodes on public sector efficiency (scores) for 35 OECD countries for the 2007-2020 period. We find that fiscal consolidations improve public sector efficiency and results are robust across efficiency models. Moreover, peripheral euro-area economies and economies with debt-to-GDP ratios between 60% and 90% are those whose public sector efficiency scores improve more when fiscal consolidation episodes occur. The evidence that fiscal consolidations enhance spending efficiency is an additional argument for fiscal consolidations, from a policy perspective.
Keywords: C23; D61; H21; E62; H63; 330; fiscal consolidation episodes; government spending efficiency; panel data; OECD